Management and restoration of pastures and rangelands in the Mediterranean basin from the Northern and the Southern perspective - El Aïch A.; Pueyo Y.; Barrantes O. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Pastoralism is a traditional land use in the Mediterranean region lasting for several thousands of years, where vegetation and animal communities are adapted to deal with summer drought periods and grazing pressure. There is a difference between the two shores of the Mediterranean in terms of pastoralism, it is more a mode of subsistence in the South, whereas in the North is a complementary activity each time less profitable. In addition, there is a clear North-South climatic gradient that determines rangelands productivity, carrying capacity, sustainable management and resilience. The environmental and socio-economical differences among the Northern and the Southern shores of the basin determine separated trends in both shores, leading to different management and future perspectives of rangelands. In addition to climate, differences in demographic pressure and socio-economical context influence rangeland status across the Mediterranean basin. Abandonment of grazing activities in North Mediterranean region vs. grazing intensification or even sedentarization in South Mediterranean region are the main socio-economical drivers, with important consequences on rangeland conservation. Despite regional differences, global warming affects the Mediterranean rangelands as a whole, increasing the shortage of water availability and the summer stress. These common perspective should promote that northern and southern rangeland managers and researchers learn from each other to deal with rangeland conservation, management and restoration. The latest research address pastoral production systems as a whole, and considers pastoral improvement techniques as a component in a holistic approach.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)